2013
DOI: 10.1002/aic.14150
|View full text |Cite
|
Sign up to set email alerts
|

Physical mechanism of sono‐Fenton process

Abstract: Hybrid advanced oxidation processes (AOPs), where two or more AOPs are applied simultaneously, are known to give effective degradation of recalcitrant organic pollutants. This article attempts to discern the physical mechanism of the hybrid sono-Fenton process with identification of links between individual mechanism of the sonolysis and Fenton process. An approach of coupling experimental results with simulations of cavitation bubble dynamics has been adopted for two textile dyes as model pollutants. Fenton p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(64 citation statements)
references
References 40 publications
2
61
0
Order By: Relevance
“…The results showed that as the static pressure increases the radical formation decreases drastically; even it becomes zero at higher ambient static pressure. This is due to at elevated static pressure, the sonochemical effects get eliminated which directly affects the generation of radical formation, provided the applied pressure must be greater than or equal to the acoustic pressure amplitude ( ≥ AW ) [9,38]. The highest…”
Section: Static Pressure Of the Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…The results showed that as the static pressure increases the radical formation decreases drastically; even it becomes zero at higher ambient static pressure. This is due to at elevated static pressure, the sonochemical effects get eliminated which directly affects the generation of radical formation, provided the applied pressure must be greater than or equal to the acoustic pressure amplitude ( ≥ AW ) [9,38]. The highest…”
Section: Static Pressure Of the Systemmentioning
confidence: 99%
“…At transient collapse, temperature and pressure reach extreme conditions, which result in dissociation of molecules to form various chemical species. To calculate the composition of the bubble at the time of collapse, we assume that thermodynamic equilibrium is attained [9]. The equilibrium mole fraction of different chemical species in the bubble at the peak conditions reached at transient collapse is estimated using Gibbs free-energy minimization technique [33].…”
Section: Cavitation Bubble Dynamics Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, semiconductor TiO 2 's simultaneous photocatalytic oxidation and reduction show significant potential due to being photoreactive, nontoxic, chemically and biologically inert, photostable, and lower in cost. Among different advanced oxidation processes (AOPs), a brand new AOP, sonolysis or hybrid AOP, combined with sonolysis has drawn increasing attention as it generates ⋅ OH free radical through transient cavitation by ultrasound irradiation [18][19][20]. Cavitation is essentially the nucleation, growth, and transient implosive collapse of gas bubbles driven by ultrasound wave.…”
Section: Introductionmentioning
confidence: 99%